Colonial Oppression and Postcolonial Trauma in Athol Fugard’s Boesman and Lena - Baqer, Zahraa Adnan; Termizi, Arbaayah binti Ali; Amin, Hasyimah binti Mohd (Journal of Posthumanism, 2025)
This paper examines postcolonial trauma in Athol Fugard’s Boesman and Lena (1969). The study primarily focuses on Fugard’s depiction of the intricate psychic complications of South African people who genuinely experienced colonial hegemony. It designates the play’s appropriation of real individuals in the context of postcolonial trauma; whereby they underwent subjective conditions which had led to the culmination of their traumatic behaviors. Therefore, the analysis sheds light on Fugard’s perception of colonialism as the crucial impetus of trauma which comes into prominence with the advent of the colonizers in South Africa. The study applies a qualitative methodology to interpret the characters as dramatic replicas of South African individuals suffering from the aftermath of colonialism. Furthermore, it follows a close reading and textual analysis of the play’s characters via polarizing Stef Craps’ concept of postcolonial trauma. Thus, the study’s main finding is exploring the characters’ trauma as a result of colonial oppression.